The Pathogenesis of Alphaviruses. (4th December 2012) - Atkins, Gregory J.
Abstract : Alphaviruses are enveloped single-stranded positive sense RNA viruses of the family Togaviridae. The genus alphavirus contains nine viruses, which are of medical, theoretical, or economic importance, and which will be considered. Sindbis virus (SINV) and Semliki Forest (SFV), although of some medical importance, have largely been studied as models of viral pathogenicity. In mice, SINV and SFV infect neurons in the central nervous system and virulent strains induce lethal encephalitis, whereas avirulent strains of SFV induce demyelination. SFV infects the developing foetus and can be teratogenic. Venezuelan Equine Encephalitis virus, Eastern Equine Encephalitis virus, and Western Equine Encephalitis virus can induce encephalitis in horses and humans. They are prevalent in the Americas and are mosquito transmitted. Ross River virus, Chikungunya virus (CHIKV), and O'nyong-nyong virus (ONNV) are prevalent in Australasia, Africa and Asia, and Africa, respectively. ONNV virus is transmitted by Anopheles mosquitoes, while the other alphaviruses are transmitted by culicine mosquitoes. CHIKV has undergone adaptation to a new mosquito host which has increased its host range beyond Africa. Salmonid alphavirus is of economic importance in the farmed salmon and trout industry. It is postulated that future advances in research on alphavirus pathogenicity will come in the field of innate immunity.